Serum proteins. Study on Mothers and Newborns at Sea Level - Medina Viglienzoni, Aída Elsa (1971)
Serum proteins in 50 pregnant women at term, apparently healthy, treated at the Callao Area Hospital were studied. The same determinations in 50 healthy newborns immediately after delivery were also made. The numbers of total proteins were slightly lower for mothers and infants. As for the alpha-2 globulin fractions and beta were significantly higher in mothers than in newborns. Gamma globulin values ​​were significantly higher in newborns than in mothers. For total, albumin and globulin proteins alpha 1, no statistically significant difference was found.